PENERAPAN BAHAN AJAR NON CETAK MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP KOMPETENSI FISIKA SISWA KELAS X MIA DI SMAN 6 PADANG - Fitria Penta Krisna; Hidayati Hidayati; Masril Masril (Universitas Negeri Padang, 2017)
Student competence in physics in classification X MIA in SMAN 6 Padang were not as expected due to several factors, teachers rarely use the variety of learning models, teachers did not facilitate students to learn in groups, teachers did not optimally facilitates students learn in groups, and teacher did not use the learning media through ICT. Therefore, the study was conducted in order to provide a solution by applying non-print instructional materials through cooperative learning type Group Investigation (GI) to increasee the student competence of physics in classification X MIA in SMAN 6 Padang.To achieve the goal of the research, we have to do quasi-experimental research with Randomized Control Group-Only Design. This research has a population are students of classification X MIA in SMAN 6 Padang enrolled in the Academic Year 2016/2017, and sampling using purposive sampling technique. The research instrument used the format observation for attitudes competence, written test for knowledge competence, and for performance using a scoring rubric for skills competence. Data were analyzed using charts analysis for the attitude competence, similarity analysis of two average for knowledge competence and skills competence.Based on the research that has been done, the results of the analysis the data obtained can be concluded that there is a difference which means applying non-print instructional materials through cooperative learning type Group Investigation (GI) to attitude competence, knowledge competence, skills competence at significant level of 0,05